The temporal gaze: the challenge for social theory in the context of GM food - Adam, Barbara (2000)
The temporal gaze in socio-environmental theory can take many forms. Time may be added to existing approaches without disturbing the status quo of theory and methodology. Alternatively, focus may be on the time-space of socio-environmental existence or typologies constructed of the complexity of socio-environmental time. Finally, phenomena, processes and events may be conceptualized as timescapes. Through the focus on genetic modification of foods, the paper demonstrates the pertinence of this timescape perspective for social theory and socio-environmental analyses. A thorough-going temporal gaze is important because a) such reconceptualization forms an integral part of rethinking the social sciences' relationship to nature and environmental matters; b) the implications at the level of theory tend to be glossed over and ignored; and c) it is central to changing practice at the level of public and personal action. The paper thus uses a timescape perspective to set out substantive and conceptual issues that present some of social theory's challenges for the new millennium. - Reproduced
Keywords: Social structure